Wiek i aktywność fizyczna mężczyzn w czasie wolnym a ich sprawność fizyczna = Age and leisure time physical activity of males and their physical condition - Jopkiewicz, Andrzej; Nowak, Stanisław Bogdan (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Physical fitness is related to the general condition of the whole human body, not only its locomotor apparatus. Fitness determines the actual ability to perform all motor activities that decide about man's vigor. It results from the beneficial and detrimental influence of ordinary physical activity and is related to health. The authors evaluated diversification of health-related fitness in adult men in relation to their age and physical activity in leisure time.
Keywords: sprawność fizyczna; aktywność fizyczna; czas wolny; mężczyźni; physical fitness; physical activity; leisure time; men